Pedagogical Considerations of Perspective Coherence Problems in Simultaneous Interpreting as a Result of Linguistic Structure, Illustrated by German-Korean Examples - Ahn, In-Kyoung (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractIn simultaneous interpreting, if the syntactic structure of the source language (hereinafter SL) and the target language (hereinafter TL) are very different, interpreters have to wait before being able to reformulate the SL segments into a meaningful utterance in TL. It is inevitable to adapt the TL structure to that of the SL so as not to unduly increase the memory load and to minimize the pause. While such adaptation facilitates simultaneous interpreting, it results in damaging the perspective coherence of the text. Discovering when such perspective coherence is impaired, and how the problem can be attenuated, will enable interpreters to enhance their performance. This paper analyses the reasons for perspective coherence damage by looking at some examples of German-Korean simultaneous interpreting, and proposes means of reducing the problem which should be sought out and practised with students during interpreter training.